Microstructure and its hardness estimation of resistance spot weld of ultra-high strength steel sheets: development of resistance spot welding with pulsed current pattern for ultra-high strength steel sheets. Issue 4 (2nd June 2020) - Matsuda, Hiroshi; Taniguchi, Koichi; Ikeda, Rinsei; Oi, Kenji
ABSTRACT: A new resistance spot welding process with 'pulsed current post-heating pattern' is developed for improving joint strength of ultra-high strength steel (UHSS) sheets. This post heating process consists of short-time high-current post-heating (pulsed current) and short-time cooling, which utilizes the phenomenon that the pulsed current reheats especially near the outer peripheral regions of the contact area of electrode/steel interfaces and faying interface of steel sheets. The strength improvement can be obtained owing to two eﬀects; the reduction of solidiﬁcation segregation in the nugget and the appropriate softening of the heat aﬀected zone (HAZ). Toughness of the nugget increases with alleviating segregation of embrittling elements. Properly widened and softened HAZ would lead to large plastic deformation, which could reduce stress concentration at the edge of the nugget on the faying interface and prevent brittle fracture in the nugget during straining. This study aims to elucidate the microstructural change in the HAZ due to the pulsed post-heating current pattern and its eﬀect on hardness proﬁles, and to propose an estimation method of HAZ hardness. 1180 MPa grade ultra-high strength steel sheet consisting of ferrite and martensite was used. Softened region was fairly widened with decreasing its minimum hardness when applying the pulsed current post heating. No signiﬁcant diﬀerence was observed in the region where the maximum temperature is over Ac1 between with and without the pulsed current post heating pattern. This would be because the maximum temperature was the same in these regions even when applying the pulsed current. The HAZ was widened in the region where the maximum temperature was lower than Ac1 . These regions have the same fractions of martensite and ferrite as the steel sheet before welding, but the martensite was much tempered when applying the pulsed current pattern. These tempered phenomena of the martensite can be well estimated using an accumulated tempering parameter for both tempering martensite and autotempering behaviour of martensite formed during cooling after welding.